Up-scale challenges on biopolymer production from waste streams by Purple Phototrophic Bacteria mixed cultures - Fradinho, Joana (2021)
Financial support from the Regional Government of Madrid through the project S2018/EMT-4344 BIOTRES-CM is gratefully acknowledged. D. Puyol wishes to thank the Spanish Ministry of Economy for the Ramon y Cajal grant. J. F